2018
DOI: 10.1073/pnas.1817325115
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotriene 2 receptor promotes endothelial permeability, tumor angiogenesis, and metastasis

Abstract: Cysteinyl leukotrienes (cys-LTs) are proinflammatory mediators that enhance vascular permeability through distinct receptors (CysLTRs). We found that CysLT2R regulates angiogenesis in isolated mouse endothelial cells (ECs) and in Matrigel implants in WT mice and enhances EC contraction and permeability via the Rho-dependent myosin light chain 2 and vascular endothelial (VE)-cadherin axis. Since solid tumors utilize aberrant angiogenesis for their growth and metastasis and their vessels exhibit vascular hyperpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 38 publications
2
50
0
2
Order By: Relevance
“…CysLTs are well known for their role in inflammation, particularly in asthma and allergic rhinitis. Recently, however, a role for CysLTs in cancer has emerged [ 9 , 21 ], with a particular focus on their role in vascular permeability and angiogenesis [ 22 ]. In a retrospective analysis, CysLT 1 antagonists, montelukast and zafirlukast, display a dose-dependent chemopreventative effect against 14 different cancers [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…CysLTs are well known for their role in inflammation, particularly in asthma and allergic rhinitis. Recently, however, a role for CysLTs in cancer has emerged [ 9 , 21 ], with a particular focus on their role in vascular permeability and angiogenesis [ 22 ]. In a retrospective analysis, CysLT 1 antagonists, montelukast and zafirlukast, display a dose-dependent chemopreventative effect against 14 different cancers [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proangiogenic activities of LTC 4 and LTD 4 were also confirmed in vivo and were found to be mediated by the engagement of CysLT 2 R on blood endothelial cells (BECs). CysLT 2 R deficiency and pharmacologic antagonism reduced tumor growth and the formation of lung metastases in a mouse model of Lewis lung carcinoma (151). These novel findings emphasize the importance of cys-LTs as non-canonical angiogenic factors in cancer.…”
Section: Canonical and Non-canonical Angiogenic Factors Produced By Bmentioning
confidence: 65%
“…These novel findings emphasize the importance of cys-LTs as non-canonical angiogenic factors in cancer. It is possible to speculate that LTC 4 released by circulating basophils can activate CysLT 2 R overexpressed in tumor BECs (151), thus contributing to angiogenesis. It has been suggested that CysLT 2 R might represent a possible pharmacologic target in tumor growth and metastases formation (151).…”
Section: Canonical and Non-canonical Angiogenic Factors Produced By Bmentioning
confidence: 99%
See 1 more Smart Citation
“…This study advanced our preclinical knowledge of our novel small molecule CysLT 1 antagonist, 1,4-dihydroxy quininib in CRC. Cysteinyl leukotrienes are bioactive lipids derived from arachidonic acid [33] and through their receptors, CysLTs enhance vascular permeability, promote inflammation and angiogenesis [33,34]. Target profiling demonstrated that similar to the parent compound quininib (Q1), 1,4-dihydroxy quininib is a CysLT 1 antagonist [21,22].…”
Section: Discussionmentioning
confidence: 99%